Effectiveness of Infection Management Control Among Children with Febrile Neutropenia - Khoirunnisa, Khoirunnisa; Allenidekania, Allenidekania; Hayati, Happy; Mulyana, Aep Maulid; Kurniawan, Kurniawan (Universitas Aisyah Pringsewu, 2023)
Febrile neutropenia mostly happens among children with cancer and can be prevented by infection management control. This study aimed to measure the parents’ knowledge and behavior about infection management control implementation in children with febrile neutropenia. This study used a pre-experimental design with a pre-post without control group approach. The study sample consisted of 30 parents of children with cancer who were treated with febrile neutropenia. Pre-test measured parents’ knowledge about infection control using Parents’ Knowledge Instrument before the education session begins. Infection management control consisted of parents’ education and behavior monitoring of infection control for five days in hospital. After that, the respondents did a post-test to see the effectiveness of the intervention. The infection management control was effective to reduce infection. This can be seen from the significant increase in parents’ knowledge (p=0,001) and it was in line with the change of parents’ infection management control behavior. Parents’ infection management control in children with febrile neutropenia is effective in reducing the incidence of infection and the length of stay for children in the hospital, as well as improving the quality of life for children. Further research can be carried out with more effective methods so that infection management control can run optimally.